Aspectos da integração regional em defesa no Cone Sul - Mathias, Suzeley Kalil [UNESP]; Guzzi, André Cavaller [UNESP]; Giannini, Renata Avelar [UNESP] (Instituto Brasileiro de Relações Internacionais, 2008)
Trata-se de avaliar como a aproximação entre os países promovendo a integração regional incide sobre qualidade da democracia e como esta se apresenta no setor de defesa e segurança. A perspectiva adotada é que o grau de estabilidade nas relações civil-militares incide diretamente sobre a formulação e desenvolvimento da cooperação em segurança regional e na estabilidade da democracia latino-americana.

Our objective in this paper is to argue the relations between civilians and military in the process of consolidation of the democracy in the South America, Argentina and Brazil in particular and how these countries promoting the integration in the defense and security areas. The perspective adopted is that the stability degree in civilian-military relations directly happens on the development of the cooperation in regional security and of course on stability of the Latin American democracy.
Aspects of regional integration on defense in South Cone
Keywords: Democracia; Defesa; Brasil; Argentina; Democracy; Defense; Security; Integration